The use of a large pharmacoepidemiological database to study exposure to oral corticosteroids and risk of fractures: validation of study population and results. - Van Staa, T; Abenhaim, L; Cooper, C; Zhang, B; Leufkens, H (2000)
Purpose - The objective of this study was an evaluation of the sensitivity of findings of the relationship between oral corticosteroid use and the risk of fracture. We found in earlier work that the risk of fracture was significantly higher during oral corticosteroid treatment, with increases of 61% in hip and 160% in vertebral fractures.Methods - Information was obtained from the General Practice Research Database which contains medical records of general practitioners in the UK. The study included 244,235 oral corticosteroid users and 244,235 controls.Results - The validation of fracture cases showed that the hip fractures, as recorded in the GPRD, were confirmed by the GP on the questionnaire in 90.7% of the cases and by discharge summary in 86.5%. The relative rate of non-vertebral fracture during oral corticosteroid use did not vary substantially between patients with different diseases, age, or gender. The sensitivity analysis, modifying the type of analysis or inclusion of patients, did not materially change the findings.Conclusions - We found a high level of validity of the GPRD with respect to hip and vertebral fractures. The sensitivity analysis indicated internal validity and consistency of the findings on fracture risks of oral corticosteroid therapy. Copyright (c) 2000 John Wiley and Sons, Ltd.